PENGETAHUAN DAN MOTIVASI MAHASISWA DI PULAU LOMBOK TERHADAP PRODUK PERBANKAN SYARIAH - Lale Ajeng Khalifatun Wardani; I Putu Septian Adi Prayuda; Fathurrahman, Fathurrahman; Slamet Mardiyanto Rahayu; Aminy, Muhammad Habibullah (Yayasan Nusantara Hasana Berdikari, 2024)
The development of sharia banking in Indonesia is very rapid. Various sharia concept products are offered to customers. Based on research in terms of knowledge, the majority of students on Lombok Island (62%) understand sharia savings and in terms of motivation, the majority of students on Lombok Island (82%) choose sharia banking products to avoid usury.